LA CULMINACIÓN DEL JUICIO ORAL LABORAL MEDIANTE LA AUDIENCIA DEFINITIVA - Jiménez Abad, Jairo Patricio (2015)
This scientific purpose in this thesis is to study and propose a solution to the problem of entitled investigation, "the culmination LABOR TRIAL BY THE FINAL HEARING" which I consider of vital importance to analyze in detail the rules in force in our country and other countries as Colombia and Venezuela. In colonial times the Ecuador has been exposed to countless abuses, the property of the inhabitants were not respected and they were subject to forced labor without remuneration. Bonds established the Spanish Crown Royal and Ordinances which aimed to optimize working conditions of indigenous peoples. Later a law of procedure for actions relating to the work, whereby jurisdiction for labor disputes was granted was issued. Concerning these issues have made a doctrinal study to verify from the origin and evolution of the oral proceedings in labor matters in Ecuador until today The information collected conceptually, doctrinal, legal and comparative law; the study of the Republic of Ecuador, the analysis of the Universal Declaration of Human Rights, the Pact of San José; the analysis of surveys and interviews with lawyers in free practice of the city of Loja, conducting a single hearing in work processes considered feasible; For this reason I propose the realization of this thesis, raising legal reform in the Labour Code.